EFEKTIFITAS BUDAYA ORGANISASI, TEKNOLOGI INFORMASI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2022)
This study aims to examine the effectiveness of accounting information systems that are influenced by organizational culture and information technology (IT) at car dealership companies in Bandung, West Java. This research was initiated by the problem of the ineffective use of accounting information system applications in several small and medium scale companies in Bandung, West Java.Descriptive method is used to describe the research results in more detail and verification method is used to test the magnitude of the influence between the variables studied. Data was collected by distributing questionnaires to the unit of analysis that became the research sample, namely car dealership companies in Bandung. Sampling using simple random sampling technique. Data analysis used multiple linear regression, while for hypothesis testing in this study using t test using SPSS 20 software.Empirically, it can be proven that information technology has an effect on the quality of accounting information systems, while organizational culture has no effect on the quality of accounting information systems.The results of this study contribute to developing an effective and comprehensive financial application model as well as a basis for developing better IT in various small and medium scale companies. Keywords: organizational culture, information technology, effectiveness of accounting information systems